A critical review of nanodiamond based nanocomposites: Synthesis, properties and applications. (15th June 2018) - Zhang, Yinhang; Rhee, Kyong Yop; Hui, David; Park, Soo-Jin
Abstract: Diamond is a metastable allotrope of carbon. Monocrystalline diamond with particle size less than 100 nm (designated as nanodiamond) has been widely studied during the past decades. Nanodiamonds have recently attracted attention owing to their exceptional mechanical and optical properties, tunable surface structure, and high specific surface area. The specific core-shell structure and abundant functional groups on its surface endow it with a variety of functional applications. Their excellent physical properties enable their application as ideal fillers in reinforcing polymer composites, resulting in superior mechanical properties, thermal stability, thermal conductivity and tribological properties. In addition to polymer composites, nanodiamonds and its composites are also widely used in sensors, optical computing, and quantum computing. As nanoscale materials, nanodiamonds and its composites are also used in electrical energy storage, wastewater treatment and bioapplications. Due to its superior biocompatibility and low cytotoxicity, nanodiamonds and its composites are now becoming crucial in biological applications. In this study, the properties of nanodiamonds and their application in polymer composites, electronics, energy, environmental areas and biological areas were analyzed.